Agricultural development policy diffusion associated with leading cadre’s experience and expansion of protected agriculture in China - Liu, Min; Qi, Danshu; Zhong, Taiyang (Frontiers in Environmental Science, 2023)
Protected agriculture has notably expanded since 2010 in China and many factors have influenced protected agricultural expansion. Yet little attention has been paid to how the successful experiences of protected agriculture demonstration areas have been diffused. Leading cadres are considered to play an important role in the policy diffusion process, yet little attention has been paid to the influence of leading cadres with connections to industry demonstration regions on industry development. Thus, this study examined the impact of mayors and municipal party secretaries connected to four protected agriculture demonstration regions – Shandong Province, Jiangsu Province, Hebei Province, and Liaoning Province – on the expansion of protected agriculture. This study used panel data from 314 prefectural-level cities and 1792 counties for the period 2014-2018 and the multidimensional fixed-effects model for a quantitative study. The results show that connected mayors significantly contribute to the expansion of protected agriculture, with the scale of protected agriculture in the county-level areas under their jurisdiction being on average 10.8% higher than that in areas under the jurisdiction of unconnected mayors. The effect of connected municipal secretaries on the expansion of protected agriculture was not significant. In addition, there were geographical differences in the impact of leading cadres on the expansion of protected agriculture. The positive impact of leading cadres on the protected agriculture expansion is significantly weakened when the area under their jurisdiction is located in the less economically developed western region or is part of the comprehensive climate unsuitable area during the March-June sowing period. The leading cadres connected to Shandong Province, Liaoning Province, and Jiangsu Province respectively had significantly different but positive impacts on the expansion of protected agriculture.